Update on morbidity and mortality in systemic sclerosis–related interstitial lung disease. Issue 1 (February 2021) - Volkmann, Elizabeth R; Fischer, Aryeh
Contemporary studies of systemic sclerosis consistently demonstrate that interstitial lung disease is a leading cause of disease-related death. This review summarizes morbidity and mortality outcomes in systemic sclerosis-related interstitial lung disease patients from high-quality observational and interventional studies over the last 50 years. The data presented suggest a trend for improved morbidity and mortality outcomes among present day systemic sclerosis–associated interstitial lung disease patients. Specifically, systemic sclerosis–associated interstitial lung disease patients appear to be living longer from the time of the initial diagnosis. Despite improved survival, the number one cause of death for most systemic sclerosis–associated interstitial lung disease patients remains respiratory failure from interstitial lung disease. This review describes the most important demographic, clinical, and biological factors, which affect mortality in systemic sclerosis–associated interstitial lung disease, and could be used to help stratify patients for closer monitoring and more aggressive initial treatment. The review concludes with an overview of future research needed to (1) understand how to personalize the care of systemic sclerosis–associated interstitial lung disease patients to improve morbidity and mortality outcomes; and (2) investigate whether novel therapeutic interventions (e.g. anti-fibrotics, hematopoietic stem cell transplantation) offer any meaningful long-term survival advantage over the current standard of care.